Clinical spectrum of dermatological disorders found in HIV-positive patients at Helen Joseph Hospital - Sibisi, Silindile Ayanda (My University, 2017)
Background The human immunodeficiency virus (HIV) epidemic is one of the world’s most significant health problems. Sub-Saharan Africa has the highest prevalence globally with an estimated 5.7- 6.7 million people in the region living with HIV (WHO, 2012). South Africa is the epicenter of the epidemic. HIV/ acquired immunodeficiency syndrome (AIDS) affect many organ systems including the skin. More than 90% of HIV infected individuals will have cutaneous manifestations of HIV at some time during their infection. These HIV- related skin conditions are often atypical in presentation, may be severe and can be poorly or non-responsive to treatment when compared to HIV-uninfected individuals. Limited studies have been conducted which describe the whole spectrum of cutaneous manifestations in HIV infected population and none have been done in Johannesburg. Objectives To describe the frequency and the spectrum of skin diseases in HIV positive patients, to correlate the clinical picture with CD4 counts and the use of antiretroviral therapy (ART). Methods This is a retrospective study. Files of 98 patients who attended the dermatology outpatient department from January 2014 to December 2014 with HIV infection were reviewed. Only 81 patients met the inclusion criteria. These were male and female adults, > 18 years of age; HIV- positive status was confirmed on antibody/ antigen tests; a CD4 cell count was available within 3-6 months, at the time of, or 3-6 months after the initial clinic visit and a clinical diagnosis of the skin condition had been verified by the senior physician/ consultant. Both those on ART and not yet on ART formed part of the study. Skin punch biopsies were taken in those patients where clinical diagnosis was difficult to make. Results A total of 25 different skin disorders were documented. Inflammatory skin disorders constituted the largest percentage of skin disorders followed by malignancies. The most frequently diagnosed skin diseases were Kaposi sarcoma, seborrheic dermatitis, papular pruritic eruption of HIV/AIDS, dermatophyte infections and drug reactions. The majority (72.8%) of patients were on ART. The frequency of skin conditions was increased in patients with CD4 counts less than 200 cells/mmᵌ. Fifty-nine patients (72.8%) of the patients were on ART when they developed the skin diseases and twenty-two (27.2%) patients were not yet on therapy. 54.3% were females and 37% were males. Conclusion In our study, skin diseases were common in patients with HIV and their frequency increases with low CD4 counts. This is the first study according to the author’s knowledge done in Johannesburg describing the spectrum of skin diseases found in patients with HIV infection.
A research report submitted to the Health Sciences, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Medicine in Dermatology. Johannesburg 2017.
Keywords: HIV